Development, Testing, and Validation of ADAS L2/L3 Systems: A KPI-Based Methodology - Leandro Ronchi; Claudio Annicchiarico; Renzo Capitani (Engineering Proceedings)
In recent years, advanced driver assistance systems (ADAS) have become increasingly popular, with the aim of significantly reducing road accidents and achieving the European Union’s goal of zero road fatalities by 2050. Level 2 and 3 ADAS systems, actively controlling vehicles rather than responding only in emergencies, are more crucial in reducing road accidents but increase system complexity and require greater investment in hardware, software development and calibration. This study proposes a consistent methodology that identifies specific KPIs to streamline the development and testing phases, both virtual and on-road. The proposed approach will be able to rapidly classify and evaluate the performance of Level 2 and Level 3 systems by reducing validation time and cost and minimizing the need for road tests.